SEMINAR PRA NIKAH DALAM UPAYA MEMAHAMI KONTEKS DIRI TERHADAP INTENSI PERGAULAN BEBAS BAGI REMAJA - Alvia, Nurmilah amalia alvia; Kusnandar, Enan (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2024)
This phenomenon, which often occurs especially in teenagers, has become a social problem in society. Forms of behavior that are not in accordance with Islamic law among teenagers have become a habit, promiscuity varies from feeling attracted to the opposite sex, dating to touching each other's sensitive parts to having sexual intercourse. One thing that can influence behavior that is not in accordance with sharia is self-control, teenagers who have high self-control tend to have a sense of responsibility to look after themselves. The function of the pre-marital seminar activity for teenagers created by students of the KPM (Community Service Lecture) Islamic Family Law study program is in an effort to understand the self-context among teenagers regarding the intention of getting pregnant outside of marriage due to promiscuity for the Kalijati village community so it is hoped that this service program will be appropriate with society.